The Role of Community Learning Activity Centers in Overcoming Social Problems - Endah Ratnawaty Chotim (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aimed to analyze the role of the Community Learning Activity Center in Overcoming Social Problems. This study uses a qualitative research method with a descriptive analysis approach. It is collecting data in this study using the form of observation, interviews, and documentation. The sample in this study used a multiple-stage random sampling method—data analysis techniques through data collection, data presentation reduction, and concluding. The main focus of the Community Learning Activity Center in this study were three main Community Learning Activity Centers, namely: 1) Jembar Kabisa Community Learning Center; 2) Guna Darma Community Learning Center; and 3) Cigembong Community Learning Center. Based on the data and research analysis, it can be concluded that the Community Learning Activity Center in Sumedang district is the Jembar Kabisa Community Learning Activity Center; Guna Darma Community Learning Center; and the Cigembong Community Learning Activity Center to overcome poverty through non-formal education in the form of valuable and practical programs, while other activities in the development and community empowerment sector exist but are still not optimal.